2022
DOI: 10.3390/plants11192548
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Salinity Stress in Maize Seedlings by the Application of Vermicompost and Sorghum Water Extracts

Abstract: Abiotic stresses are important constraints limiting crop productivity worldwide. Salinity is one of the most devastating environmental factors restraining the production of crops. It is urgently needed to search for environmentally safe and sustainable approaches to mitigate the harmful effects of salinity on plants. Hence, applying vermicompost and low-dose aqueous extract of sorghum delivers a pragmatic solution to ameliorate the detrimental outcomes of salinity on maize seedlings (Zea mays L.). The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Similarly, various other authors also found that organic manure application enhanced the chlorophyll contents and antioxidant activities and reduced the oxidative damage in different plants [186,187]. In addition, the use of organic fertilizers under saline conditions also increases the microbial population and gene expression, boosting biomass productivity and salt tolerance in plants [188].…”
Section: Crop Saline Stress Organic Fertilizers Major Effects Referencesmentioning
confidence: 72%
“…Similarly, various other authors also found that organic manure application enhanced the chlorophyll contents and antioxidant activities and reduced the oxidative damage in different plants [186,187]. In addition, the use of organic fertilizers under saline conditions also increases the microbial population and gene expression, boosting biomass productivity and salt tolerance in plants [188].…”
Section: Crop Saline Stress Organic Fertilizers Major Effects Referencesmentioning
confidence: 72%
“…The use of vermicompost and sorghum water extract has contributed to the growth of maize seed. This was attributed to an increase in photosynthetic pigments and antioxidant (SOD, POD and CAT) activities (Alamer et al, 2022).…”
Section: Peroxidasementioning
confidence: 99%
“…Applying VC, either through foliar or edaphic methods, bolsters the activity of antioxidant enzymes, namely SOD, POD, and CAT [108]. This leads to a decrease in EL and oxidative stress and benefits maize seedling growth [146]. Furthermore, applications of FYM + PM under salinity stress notably enhance antioxidant activities, elevating CAT and APX levels by 59.9% and 68.8%, respectively.…”
Section: Organic Amendments Improve Antioxidant Activitiesmentioning
confidence: 99%